Project finance in theory and practice : designing, structuring, and financing private and public projects - Gatti, Stefano, 1967- (Academic Press, 2013)
This book presents comprehensive coverage of project finance in Europe and North America. The Second Edition features two new case studies, all new pedagogical supplements including end-of-chapter questions and answers, and insights into the recent market downturn. The author provides a complete description of the ways a project finance deal can be organized-from industrial, legal, and financial standpoints-and the alternatives available for funding it. After reviewing recent advances in project finance theory, he provides illustrations and case studies. At key points Gatti brings in other project finance experts who share their specialized knowledge on the legal issues and the role of advisors in project finance deals. Foreword by William Megginson, Professor and Rainbolt Chair in Finance, Price College of Business, The University of Oklahoma. Comprehensive coverage of theory and practice of project finance as it is practiced today in Europe and North America. Website contains interactive spreadsheets so that readers can input data and run and compare various scenarios, including up to the minute treatment of the cutting-edge areas of PPPs and the new problems raised by Basel II related to credit risk measurement.